The Determination of National Disaster Status under Law Number 24 of 2007 on Disaster Management: An Analysis from the Perspective of Siyasah Dusturiyah - Fidya Rizka Meylanti; Chaerul Shaleh; Taufiq Alamsyah (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study is motivated by the ambiguity of Article 7 paragraph (2) of Law Number 24 of 2007 on Disaster Management, which stipulates five indicators for determining national disaster status namely the number of casualties, property losses, damage to infrastructure, the extent of affected areas, and socio-economic impacts without providing binding quantitative thresholds. This normative ambiguity grants excessively broad executive discretion and has resulted in inconsistent treatment of major disaster events in Indonesia. The study aims to analyze the application of attributed authority in determining national disaster status, examine the procedures for establishing disaster indicators under Law Number 24 of 2007, and assess the issue from the perspective of Siyasah Dusturiyah. This research employs a normative juridical method using statutory and conceptual approaches with a descriptive-analytical design. Data were analyzed using the interactive model developed by Miles, Huberman, and Saldana. The findings reveal that the President's authority to declare a national disaster derives from constitutionally attributed powers inherent to the office; however, such authority is not supported by an adequate disaster risk governance mechanism. Consequently, the risk assessment process becomes disconnected from the risk evaluation stage due to the absence of binding quantitative parameters. From the perspective of Siyasah Dusturiyah, such attributed authority is justifiable as a mandate to safeguard public welfare (maslahah). Nevertheless, without objective standards, it lies on a delicate boundary between legitimate ijtihad and arbitrary executive discretion. This study concludes that the ambiguity of the indicators set forth in Article 7 paragraph (2) constitutes a systemic deficiency in Indonesia's disaster governance framework. It therefore recommends reformulating the provision by establishing clear, measurable, and accountable quantitative thresholds to strengthen legal certainty, transparency, and accountability in determining national disaster status.